Hyper-parallel tempering Monte Carlo simulations of Ar adsorption in new models of microporous non-graphitizing activated carbon: effect of microporosity - Terzyk, A.; Furmaniak, S.; Gauden, P.; Harris, P.; Wloch, J.; Kowalczyk, Poitr (IOP Publishing Ltd, 2007)
The adsorption of gases on microporous carbons is still poorly understood, partly because the structure of these carbons is not well known. Here, a model of microporous carbons based on fullerene-like fragments is used as the basis for a theoretical study of Ar adsorption on carbon. First, a simulation box was constructed, containing a plausible arrangement of carbon fragments. Next, using a new Monte Carlo simulation algorithm, two types of carbon fragments were gradually placed into the initial structure to increase its microporosity. Thirty six different microporous carbon structures were generated in this way. Using the method proposed recently by Bhattacharya and Gubbins (BG), the micropore size distributions of the obtained carbon models and the average micropore diameters were calculated. For ten chosen structures, Ar adsorption isotherms (87 K) were simulated via the hyper-parallel tempering Monte Carlo simulation method. The isotherms obtained in this way were described by widely applied methods of microporous carbon characterisation, i.e. Nguyen and Do, Horvath–Kawazoe, high-resolution as plots, adsorption potential distributions and the Dubinin–Astakhov (DA) equation. From simulated isotherms described by the DA equation, the average micropore diameters were